Two‐dimensional knowledge‐based volumetric reconstruction of the right ventricle documents short‐term improvement in pulmonary hypertension. Issue 6 (13th June 2017) - Schwaiger, Johannes P.; Knight, Daniel S.; Kaier, Thomas; Gallimore, Adele; Denton, Christopher P.; Schreiber, Benjamin E.; Handler, Clive; Coghlan, John G.
Abstract : Background: Data are scarce about short‐term right ventricular changes in pulmonary hypertension. Two‐dimensional knowledge‐based reconstruction of the right ventricle with 2D echocardiography (2DKBR) has been shown to be a valid alternative to Cardiac MRI. Patients and Methods: In this longitudinal study 25 pulmonary hypertension patients underwent 2DKBR of the right ventricle, assessment of NT‐proBNP levels and functional class at baseline and after a mean follow‐up of 6.1 months. Patients were followed up clinically for a further mean of 8.2 months. The majority of patients had connective tissue disease (CTD) associated pulmonary arterial hypertension (n=15) or chronic thromboembolic pulmonary hypertension (CTEPH; n=6). A total of 15 patients underwent an intervention, either new targeted therapy, escalation of targeted therapy or pulmonary endarterectomy. A total of 10 clinically stable patients were routinely followed up without any change in therapy. Results: There were significant improvements in the right ventricular end‐diastolic volume index (111±29 mL/m² vs 100±36 mL/m²; P =.038), end‐systolic volume index (72±23 mL/m² vs 61±25 mL/m²; P =.001), and ejection fraction (35±10% vs 40±9%; P =.030). Changes in NT‐proBNP levels correlated strongest with changes in end‐systolic volume index ( r =−.77; P =<.0001). Four patients experienced clinical worsening during extended follow‐up, dilatation of the right ventricle was associated with clinical worsening. Conclusion: In a CTD and CTEPH dominated patient population significant reverse remodeling and improvement of ejection fraction occurred despite a short follow‐up and was paralleled by significant changes in NT‐proBNP levels. Further right ventricular dilatation was associated with worse clinical outcome. 2DKBR is a feasible substitute for Cardiac MRI to follow‐up right ventricular indices in pulmonary hypertension.